Improvement of safety measures by applying a technical solution on the M-80A infantry combat vehicle - Končar, Milan N.; Anarbaev, Odil I.; Mutavdžić, Dobrivoje R.; Lazić, Goran M.; Jokić, Željko M. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: The paper presents a solution for overcoming a possible problem - breach of safety measures when operating the BVP M-80A Infantry Combat Vehicle on a training ground during tactical exercises and shooting at night. The crux of the problem is that the officer in charge of a tactical exercise and shooting is not in a position to observe in which direction the gunner-operator aims because no device has been installed on the BVP M-80A to signal this.Methods: After deploying the vehicle in practice and and on the basis of experience during shooting, it was concluded that there is a problem of controlling shooting at night and in reduced visibility conditions.Results: The paper provides a practical solution to prevent situations such as disorientation, impossibility of observing targets, and turning weapons towards the outside the shooting range boundaries, thus violating the security measures of all participants in the exercise including the BVP M-80A unit itself. A technical improvement was implemented on the vehicle by installing a signaling device that gives visual information to the officer in charge of shooting in which direction the weapon is turned.Conclusion: The installed signaling device enables the officer who commands the exercise and shooting to be in control in a timely manner, eliminate possible causes of violation of security measures, and successfully implement the planned activity.
Keywords: security measures; control; combat vehicle; technical improvement; signaling device